PROBLEMATIKA PEMBELAJARAN AGAMA ISLAM SUKU ANAK DALAM DI SAROLANGUN, JAMBI - Abdul Mukti; Sutarto Sutarto; Rahmat Iswanto (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2022)
This study aimed to find a depiction of the problems encountered in learning Islamic religious education for the Anak Dalam Tribe at SDN 204 Tanjung Raden III Suka Damai Village and to find solutions to overcome the problems of PAI learning. This study used a qualitative approach. The participants incorporated the principal, PAI teachers, and Anak Dalam Tribe students. Data collection techniques deployed observations, interviews and documentation. The data were analyzed resting upon the following stages: data reduction, data presentation, and conclusion drawing. This study conclusively revealed that the problems encountered in Anak Dalam Tribe’s PAI learning included: lack of motivation in following PAI lessons, lack of awareness to practice Islamic teachings, Teachers’ education qualifications that were still low, minimal infrastructure, and the environment which was dominated by non-Muslims. The efforts made to overcome various problems were motivating students, creating a conducive learning atmosphere, practicing Islamic teachings, improving the quality of teachers, completing educational facilities and infrastructure, and building cooperation with the parents of Anak Dalam Tribe.